please anwer this question sir
Asked by ramhari | 27th Apr, 2010, 02:33: PM
(7x4 + 13/4x3 + x2 + 2x - 1 )2009
( 2x + B )2009 where B = 7x4 + 13/4x3 + x2 - 1
= B2009 + 2009B2008(2x) + ................
Now, the term,
2009B2008(2x) will give (-1)2008 = 1 for the -1 in expression for B.
Hence the coefficient of x is,
2009x2 = 4018.
Answered by | 27th Apr, 2010, 11:43: PM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number